Relief Dissection Potential and its Relationship with Geodiversity in a Karstic Region of Brazil - Souza, Fabiano Vieira de; Ruchkysa, Úrsula de Azevedo; Fonseca, Bráulio Magalhães; Lobo, Carlos (Sociedade & Natureza, 2023)
The quantification of abiotic features is a process in Geodiversity focused studies to indicate priority areas for conservation. Although some quantification methods are in use, doubts remain as to their applicability, particularly the relationship between coefficients of geodiversity and rugosity. In this perspective, this study proposes to analyze this relationship through the geostatistical models of Local Moran’s I and Geographically Weighted Regression (GWR), applied in sub-basins of one of the most important karstic regions in Brazil. To simulate the rugosity coefficient, the Global Relief Dissection Index was used, which consists of a combination of morphometric indices that enable the estimation of a given region’s power of dissection. The application of Local Moran’s I showed geodiversity and relief dissection potential behavior patterns, demonstrating that the variables have spatial dependence and are correlated at certain points. The application of GWR was successful, although the model was not able to explain the regional relationship between the coefficients of geodiversity and relief dissection. Nevertheless, it enabled local analysis of different behaviors through the spatialization of local R2 and residuals. It can be inferred that there are other variables that interfere in the local geodiversity, especially, for being a geosystem with characteristics specific.